Microbial neuraminidase induces TLR4-dependent long-term immune priming in the brain. - Fernández-Arjona, María del Mar; León-Rodríguez, Ana; Mateos-Grondona, Jesús; López-Ávalos, María Dolores (Frontiers Media, 2022)
Innate immune memory explains the plasticity of immune responses after repeated immune stimulation, leading to either enhanced or suppressed immune responses. This process has been extensively reported in peripheral immune cells and also in the brain. Here we explored two relevant aspects of brain immune priming: its persistence over time and its dependence on TLR receptors. For this purpose, we used an experimental paradigm consisting in applying two inflammatory stimuli three months apart. Wild type, toll-like receptor (TLR) 4 and TLR2 mutant strains were used. The priming stimulus was the intracerebroventricular injection of neuraminidase (an enzyme that is present in various pathogens able to provoke brain infections), which triggers an acute inflammatory process in the brain. The second stimulus was the intraperitoneal injection of lipopolysaccharide (a TLR4 ligand) or Pam3CSK4 (a TLR2 ligand). One day after the second inflammatory challenge the immune response in the brain was examined. In wild type mice, microglial and astroglial density, as well as the expression of 4 out of 5 pro-inflammatory genes studied (TNFa, IL1b, Gal-3, and NLRP3), were increased in mice that received the double stimulus compared to those exposed only to the second one, which were initially injected with saline instead of neuraminidase. Such enhanced response suggests immune training in the brain, which lasts at least 3 months. On the other hand, TLR2 mutants under the same experimental design displayed an enhanced immune response quite similar to that of wild type mice. However, in TLR4 mutant mice the response after the second immune challenge was largely dampened, indicating the pivotal role of this receptor in the establishment of immune priming. Our results demonstrate that neuraminidase-induced inflammation primes an enhanced immune response in the brain to a subsequent immune challenge, immune training that endures and that is largely dependent on TLR4 receptor.
Keywords: Neuroglia; Sistema nervioso - Inflamación; Virus de la gripe; Inmunología; Microglia; Neuraminidase; Neuroinflammation; TLR2; TLR4; Mouse; Immune priming